Mental health problems among adolescents and young adults with childhood-onset physical disabilities: A scoping review - Lal, Shalini; Tremblay, Stephanie; Starcevic, Danielle; Mauger-Lavigne, Melina; Anaby, Dana (Frontiers in Rehabilitation Sciences, 2022)
Aim: This scoping review aims to better understand the extent and nature of research activity on the topic of mental health problems in young people with childhood-onset physical disabilities. Specifically, we document what has been investigated in terms of the occurrence and experience of mental health problems among young people with childhood-onset physical disabilities, and their access to mental health services. Methods: We searched four databases (Medline, PsycINFO, CINAHL, Embase) for articles published between 2007 and 2019. Studies were included if they addressed: 1) young people between the ages of 13 and 24 with a childhood-onset physical disability, and 2) mental health assessment, treatment, or service access and use. Results: We identified 33 peer-reviewed studies that focused mainly on young people with cerebral palsy, arthritis, and spina bifida. The most common mental health problems investigated were depression and mood related difficulties (73%), anxiety (39%), and social/behavioural issues (33%) and the most common age range was 13 to 17. Ten studies explored access, use, and experiences of mental health services; stigma; caregiver mental health; and value for comprehensive care, using qualitative, quantitative, or mixed methods. Conclusions: Findings suggest the importance of developing integrated models of service delivery to identify and address the mental health needs of this population, and consensus on best practices for assessment and reporting rates of subclinical symptoms and psychiatric conditions.